Salmonella oranienburg and S. typhimurium in bile of apparently healthy cattle (Bos taurus) - Xavier, Vicente Leite; Campelo, José Carlos Ferreira (Pesquisa Agropecuaria Brasileira, 2014)
This article deals with bacteriological studies aiming at identifying Salmonella carriers among apparently normal bovines. The authors examined the bile from four year old males from Governador Valadares in Minas Gerais, and Araçatuba in São Paulo. Samples were collected at the Santa Cruz slaughter house in Rio de Janeiro, Brazil. Procedures are given for collecting the specimen (gall bladder), and isolating, identifying and typeing the Salmonella oranienburg (three strains) and S. typhimurium (one strain, see Addendum) studied. These procedures (including the use of enrichment and selective media, biochemical and serologic tests) are, on the whole, those adopted and advocated by Kauffmann (1941, 1951, 1954, 1966), Galton et al. (1950) and Edwards and Ewing (1951, 1955, 1962). The serologic tests were carried out with sera from Edwards (Communicable Disease Center, Atlanta, Ga., U.S.A.) and single “O" 7 serum (for aiding S. oranienburg identification) prepared at the Escola Nacional de Veterinária (Universidade Federal Rural do Rio de Janeiro, Ministério da Educação e Cultura, Brasil). Standard cultures were kindly provided by Edwards. The authors discuss the importance of their findings in the epidemiological field, and the possible significance of it in the area of serologia diagnosis and preventive treatment. Several valuable contributions from specialized literature on S. oranienburg, are reviewed emphasizing names, year of publication and the source of infection. References on S. typhimurium are given too (see Addendum).